Knowing God by experience: the spiritual senses in the theology of William of Auxerre - Coolman, Boyd Taylor (Catholic University of America Press, 2004)
A synaesthetic beatific vision -- The manifold effects of the metaphysical good -- The Trinity as manifold delectable -- Creation : the manifestation of the delectabilia divina -- The virtue of faith : knowledge of God in a visual mode -- The virtue of charity : love of God in a tactile mode -- Symbolic theology : exterior perception of God's effects -- Mystical theology : interior perception of God's effects -- Taste and see : the spiritual senses and the Eucharist -- Conclusion : spiritual apprehension : the spiritual senses and the knowledge of God